‘Fill the Earth and subdue it…Have Dominion’ Gen.1:28: Environmental Violence and the Theology of Ecology. - Musana, Paddy (East African Journal of Traditions, Culture and Religion, 2022)
The world today, never as ever before, stands at the gates of human-instigated destruction. In living to our divine mandate of subduing and dominating the earth, as enshrined in the Bible text (Gen.1:28), we have overstepped all the principles that would grant self-regeneration of the universe. Through individualistic and nationalistic interests, humans have set out on an exploitative undertaking of the natural resources without limit and consideration. The intricate universe with its pre-set principles groans under the weight of unregulated degradation through human ‘inventions’ and manipulations. The reality of climate change and the call for mitigation measures is met with denial and derision especially by individuals who are set to exploiting resources to the extreme. Given the reality of overexploitation and destruction, there is need for reflection. This should be a reflection based on the interpretation and implications of the human mandates as stated in the text quoted above. Such a reflection is guided by seeing the universe as a gift of the Creator to His subjects who should use and maintain resources in a manner that reflects responsibility. The purpose of this article is a call to critical reflection on the need of religious institutions, using their scriptures and doctrines, to actively participate in environmental protection and climate change mitigation measures.